Adult root structure of mediterranean shrubs: relationship with post‐fire regenerative syndrome. (22nd July 2013) - Saura‐Mas, S.; Lloret, F.; Elzenga, T.
Abstract Life‐history attributes can impose differences on root system structures and properties related to nutrient and water uptake. Here, we assess whether plants with different post‐fire regenerative strategies (resprouters, seeders and seeder–resprouters) differ in the topological and morphological properties of their root systems (external path, altitude, magnitude, topological index, specific root length, root length, root‐to‐shoot biomass ratio, length of the main axis of the root system and link length). To achieve these objectives, we sampled individuals from eight woody species in a shrubland located in the western Mediterranean Basin. We sampled the adult root systems using manual field excavation with the aid of an air compressor. The results indicate that resprouters have a higher root‐to‐shoot ratio, confirming their higher ability to store water, starch and nutrients and to invest in the belowground biomass. Moreover, this pattern would allow them to explore deeper parts of the soil layers. Seeder species would benefit from a higher specific root length, pointing to increased relative root growth and water uptake rates. This study confirms that seeders and resprouters may differ in nutrient and water uptake ability according to the characteristics of their root system. Species that can both resprout and establish seedlings after fire had different patterns of root system structure; in particular, root:shoot ratio was more similar to resprouters and specific root length was closer to seeders, supporting the distinct functional performance of this type of species.